Effects of Bee Pollen on the Technical and Allocative Efficiency of Meat Production of Ross 308 Broiler - Hashmi , Muhmmad Sadiq; Haseik, Peter; Elimam, Ibrahim; Garlik, Jozef; Marek, Bobko; Miroslava, Kaeaniova (International Journal of Poultry Science, 2012)
Productivity and efficiency are the most important aspects helpful in making decisions about production and selection of inputs. Ultimately, the most efficient production ensures more profit of any business. The business of chicken production is one of the profit earning businesses. The sustainability which ensures the existence of the firms as well as promises the availability of food and fiber depends on the efficient use of input puddles. With reference to cost minimization and profit maximization, poultry feed which takes the major portion of the total cost is extremely important. This research was done to see the effects of bee pollen on the poultry meat production efficiency (technical as well as allocative efficiency). On the basis of data of input quantities (feed) and output quantities (meat of different parts of chicken), technical efficiency was measured. Additionally, in order to see the allocative efficiency, prices of inputs (feed) and outputs (each part of chicken meat) were considered. After analyzing the average efficiency scores, it was found that group P1 of chicken which was supplemented with bee pollen as 5g kg-1 of feed mixture, got the maximum average efficiency scores as 0.9732 and the control group (K) got the 2nd level. It was concluded that use of bee pollen has limited positive effect i.e., use of bee pollen 5 g kg-1 of feed mixture has positive effect and when its use is more than 5 g kg-1 of feed mixture then its effect is negative. As the amount of bee pollen is increased, the average efficiency score decreases continuously.